Leadership Authority Research Trends and Issues 2000-2003: A Bibiliometric Analysis - Ginting, Sunardi; Naim, Sidrotun; Asrarudin, Asrarudin; Dhamayanti, Sylvia Kartika; Nuraeni, Yayang Ayu (Borong Newinera Publisher, 2026)
Authoritatian leadership as a way to push others to do something within a group to achieve a goal. The main objective of this study is to identify trends and directions in research on leadership authority in organizations through a systematic review of previous studies using bibliometrics analysis. In addition, this study also identifies key topic clusters and explores research trends from recent years. The sample used consists of 593 articles sourced from the Scopus and Crossref databates, obtained through the Publish or Perish software and analyzed using VOSviewer. The analysis results reveal that nine clusters were identified, with authority and leadership emerging as the most dominant topics. However, to support the novelty of the research, several supporting factors related to leadership authority are needed, such as connections to educations aspect, healthcare and leadership transformation, which are among the most frequantly studied aspects of leadership authority. Research trends over the years show a shift in focus from the theoretical framework of leadership authority. The analysis of research opportunities indicates that there is still ample room for further studies, especially on how theory relates to practice and how leadership systems, including authoritarian leadership styles are implemented. Overall, this analysis offers a comprehensive perspective and provides new directions for future research, contributing to the development of more sustainable and efficient solutions.